Seabird digestive physiology in relation to foraging ecology - Jackson, Susan (Percy FitzPatrick Institute of African Ornithology, 2016)
This study addresses the question: are seabirds digestive opportunists or specialists? The extent of specialization in seabird digestive processes to different diets and foraging methods, is investigated experimentally. Gut passage rates of different food types of tested in vitro digestibility may reflect dietary specialization, with favoured prey types excreted more rapidly than less frequently encountered prey. Mean retention times of solid digesta are significantly correlated with foraging trip duration, and with gut length. Gut length and volume in tum scale with body mass. Assimilation efficiencies of various dietary components are not predictable purely on the basis of food composition, and show a high degree of inter- and intraspecific variability. Energy assimilation efficiency does not reflect dietary specialization, and may be maintained at approximately 75% regardless of diet. Assimilation efficiency is, however, temporarily elevated in energetically-stressed birds, such as penguins that have recently completed moult. Digestive specializations are reflected in seabirds' abilities to assimilate substances specific to certain prey organisms. Unlike most terrestrial vertebrates, seabirds are able to digest wax esters, compounds important in marine food webs. Procellariiforms exhibit unique gastric adaptations facilitating extended foraging trips and efficient transport of food to their young, both important advantages for predators exploiting patchy and unpredictable food resources. Seabirds which naturally feed on crustaceans secrete the specific enzyme chitinase from their gastric mucosae, permitting digestion of the chitinous exoskeleton of the prey. The ability to secrete this enzyme is probably a retained ancestral trait rather than a newly evolved one, and may have been lost by seabirds that do not prey on crustaceans. Differences between penguins and procellarids reflect unique adaptations to the different foraging techniques employed by these two families. The synthesis of the thesis explores the adaptive significance of gut passage rate and allometry of the gut in relation to the two predominant foraging techniques employed by seabirds: long- distance aerial soaring and subsurface swimming. Scaling of seabird gut size may play an important role in the interplay between metabolic rate, the energy demands of foraging, and digestive physiology. The allometric approach taken here is potentially useful for studies of seabird digestion, and has application in studies linking the evolution of avian body size, and foraging ecology.